2014
DOI: 10.5152/jtgga.2014.14083
|View full text |Cite
|
Sign up to set email alerts
|

Left lateral position and common gynecologic examining position in anal manometry measurements for evaluation of urogynecologic patients

Abstract: Objective:The aim of this study is to compare the anometrical parameters obtained in the left lateral position, which is the conventional position of anal manometry, with the same measurements taken in the common gynecologic examining position (45° sitting position in a birthing chair with maximum hip flexion). Material and Methods:Twenty-one patients with lower urinary tract symptoms (LUTS) were enrolled into this prospective cohort study. Basal mean resting pressure (BMRP), maximum squeeze pressure (MSP), re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…Halani et al [ 25 ] reported that although there was no significant difference in the rectal volume measured in the left-lateral position compared with the lithotomy position in female FI patients, higher values for the measurements were observed in lithotomy than in the left-lateral position. Another study of urogynecological patients reported similar results [ 26 ]. In these studies, testing was performed first in the left-lateral position and then in the lithotomy position.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Halani et al [ 25 ] reported that although there was no significant difference in the rectal volume measured in the left-lateral position compared with the lithotomy position in female FI patients, higher values for the measurements were observed in lithotomy than in the left-lateral position. Another study of urogynecological patients reported similar results [ 26 ]. In these studies, testing was performed first in the left-lateral position and then in the lithotomy position.…”
Section: Discussionsupporting
confidence: 67%
“…In our study, DDV and MTV were signi cantly higher in the erect position than in the left-lateral position in the 80 FI patients. The reason is unclear however, but testing was performed in the same sequence as previous studies [21,22], rst in the left-lateral position and then in the lithotomy position, which may have blunted rectal sensation during rectal capacity examination in the erect position. The order of examination should be reversed and re-examined in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Halani et al [21] reported that although there was no signi cant difference in the rectal volume measured in the left-lateral position compared with the lithotomy position in female FI patients, higher values for the measurements were observed in lithotomy than in the left-lateral position. Another study of urogynecological patients reported similar results [22]. In these studies, testing was performed rst in the left-lateral position and then in the lithotomy position.…”
Section: Discussionmentioning
confidence: 64%
“…Whilst there is evidence in the literature that hip flexion alters the anorectal angle [15] as well as the activity and functionality of the pelvic floor [16], there is little to none empirically quantifying the degree or nature of alteration in the left lateral position when compared with the standard supine position. The complexity of this issue is compounded by the fact that merely moving the position of the body from left lateral to supine, even without flexion of the hips, has in itself been found to significantly move some elements of the abdominal and pelvic anatomy [17,18]. Although we are unable to quantify the effect this may have had on the fidelity of the models to the anatomy in the relevant position, we mitigated this error by aligning the anatomy with the data captured from position and pressure sensors, particularly during initial finger insertion through the anal canal.…”
Section: Discussionmentioning
confidence: 99%